Il ruolo delle emozioni nella web reputation: il caso della comunicazione digitale vaticana - Anzelmo, Angela (Rivista Italiana di Filosofia del Linguaggio, 2020)
Our contribution offers to examine the investment of emotions by the Dicastery for the Vatican’s communication (instituted by Pope Francis on June 17th 2015) to study their consequences in terms of credibility and visibility via new technologies. If the politico-religious rhetoric aims at being efficient, and that «saying.» is closely linked to «believing», to «doing» and to «having it done», it is therefore a question of understanding how institutional discourses operate on individuals in so far as they present values on communication[1] level as well as on manipulative level and seek to bring about an action, a doing of the public in the interactive space of social networks. As it develops more and more appealing techniques that are likely to cause emotion, to create empathy, as the construction of images imprints the memory and the imagination of its users, the Vatican institution appears to have succeeded in rallying the affectivity of its publics by contributing to build a strong communication pact. If emotion constitutes a means to directly reach the masses, considering that in terms of trends, popular culture is of an emotional sort, such an investment can therefore reach the believers as well as the non-believers when captured emotional expressions aspire to be shared. Through the study of the user’s reception process and starting from the relationship between medium and speech, my work focuses on strategic projections from media and digital logic when the latter invests the emotional level to promote the circulation of speeches. [1] Istituito da papa Francesco il 27 giugno 2015.